The study of torrefaction in air and steam biomass gasification for syngas production through process simulation - Yong, Yung Sheng; Ruwaida, Abdul Rasid; Ismail, Mazni (AIP Publishing, 2023)
Torrefaction is a process where biomass is converted to solid biofuel that can be sustainably used for energy generation to produce syngas. Limited information was found for a system with the combination of torrefaction and gasification. Therefore, a study by using a thermodynamic tool was conducted to study the best conditions of such system for empty fruit bunch (EFB). Four case studies were conducted for air gasification with and without torrefaction as Cases 1 and 2 respectively, steam gasification with and without torrefaction as Cases 3 and 4 respectively with varying equivalence ratio (ER), and steam-to-biomass (S/B) ratio applied in a process simulation model that is thermodynamic-based. It was found that the best case is Case 3 which increases the syngas concentration and higher heating value (HHV) by 4% and 0.4%, respectively, compared to Case 1. Therefore, steam gasification with torrefaction is the best method for syngas production.